The Impact of State-Level Research and Development Tax Credits on the Quantity and Quality of Entrepreneurship. Issue 2 (May 2020) - Fazio, Catherine; Guzman, Jorge; Stern, Scott
U.S. states often cite the acceleration of start-up activity as a rationale for the research and development (R&D) tax credit. While a strong empirical base links the R&D tax credit to increased innovation, prior work provides no causal evidence that the credit effects the rate of formation and growth potential of new businesses. This article combines data from the Startup Cartography Project with the Panel Database on Incentives and Taxes to implement a difference-in-differences estimate of the impact of state R&D tax credits on the quantity and quality-adjusted quantity of entrepreneurship. The authors find that the R&D tax credit is associated with a significant long-term impact on both. In contrast, the authors observe that state investment tax credits have no impact on the quantity of entrepreneurship and lead to a marked decline in the rate of formation of growth-oriented start-ups over time. The results indicate the potential of state R&D tax credits to stimulate entrepreneurship.